2023
DOI: 10.1177/15330338231205999
|View full text |Cite
|
Sign up to set email alerts
|

The Emerging Role of Exosomal miRNAs as Biomarkers for Early Cancer Detection: A Comprehensive Literature Review

Ali Jafari,
Keyvan Karimabadi,
Aso Rahimi
et al.

Abstract: A significant number of cancer-related deaths are recorded globally each year, despite attempts to cure this illness. Medical science is working to develop new medication therapies as well as to find ways to identify this illness as early as possible, even using noninvasive techniques. Early detection of cancer can greatly aid its treatment. Studies into cancer diagnosis and therapy have recently shifted their focus to exosome (EXO) biomarkers, which comprise numerous RNA and proteins. EXOs are minuscule goble… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 210 publications
0
5
0
Order By: Relevance
“… 190 The most extensively studied area is miRNA, and Jafari et al. 191 provided a detailed review of the application of extracellular vesicle miRNA as a biomarker in early cancer diagnosis. zNF587B plays a crucial role in early ovarian cancer detection.…”
Section: Exosome Biomarkersmentioning
confidence: 99%
“… 190 The most extensively studied area is miRNA, and Jafari et al. 191 provided a detailed review of the application of extracellular vesicle miRNA as a biomarker in early cancer diagnosis. zNF587B plays a crucial role in early ovarian cancer detection.…”
Section: Exosome Biomarkersmentioning
confidence: 99%
“…Exosomes can be used as biomarkers for different diseases such as cancers. As exosomes are present in most body fluids, they can be isolated non-invasively, therefore, their content such as RNAs and proteins can be used for prognostic and diagnostic purposes [ 5 ]. Exosomes derived from tumor contain exact information about tumor status [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…As exosomes are present in most body fluids, they can be isolated non-invasively, therefore, their content such as RNAs and proteins can be used for prognostic and diagnostic purposes [ 5 ]. Exosomes derived from tumor contain exact information about tumor status [ 5 ]. In addition, cell status may affect the level of exosomes production and content.…”
Section: Introductionmentioning
confidence: 99%
“… 8 , 9 Moreover, exosomes have a significant advantage as diagnostic biomarkers because they are present in various body fluids, can be collected non-invasively, and can be used in clinical trials. 10 Recent studies have shown that exosomes in saliva and the isolation of small extracellular vesicles using a bead-assisted platform have great potential and flexibility for tumor diagnosis. 11 , 12 circRNA (Circular RNA) lacks the 5′ cap and 3′ polytope tail, forming a closed ring structure.…”
Section: Introductionmentioning
confidence: 99%